Association of adipokines with rheumatic disease activity indexes and periodontal disease in patients with early rheumatoid arthritis and their first‐degree relatives (2019)
Objective To evaluate the adipokine levels in early rheumatoid arthritis (eRA) and first‐degree relatives (FDR) of patients with RA and establish their association with rheumatic disease activity and periodontal variables. Method A cross‐sectional study with eRA patients, FDR and a healthy population. Adipokine levels, clinical, joint radiological indexes and periodontal variables were evaluated. A descriptive, bivariate analysis was performed based on the adipokine levels by χ2, Fisher's test and Mann–Whitney U test. A logistic regression was made for associations. Results High leptin levels were associated with the diagnosis of eRA (odds ratio [OR] = 2.79; 95% CI 1.54‐5.07). Early rheumatoid arthritis with high adiponectin levels was less likely to have Multidimensional Health Assessment Questionnaire score >3, body mass index (BMI) >25 and Routine Assessment of Patient Index Data 3 score >12 (OR = 0.16; 95% CI 0.03‐0.72). Early rheumatoid arthritis was more likely to present high leptin and interleukin (IL)6 levels with low adiponectin simultaneously (OR = 5.03; 95% CI 1.05‐24.0). High leptin levels were associated with the FDR adjusted for IgG2 Porphyromonas gingivalis, swollen joints, P gingivalis and low IL6 (OR = 2.57; 95% CI 1.14‐5.95). Conclusion High adipokine levels in eRA may modulate the disease activity. Having more than 1 adipokine at high serum levels is associated with increased disability, disease activity and BMI, indicating that RA is controlled by adiponectin levels in the early stages of the disease. High leptin levels, presence of P gingivalis and swollen joints may be the factors associated with the development of RA in FDR.